IDEOLOGI ISLAM TRADISIONALIS DAN TRANSFORMASINYA DI INDONESIA - Abdullah Yaqin (Pascasarjana UIN Kiai Haji Achmad Siddiq Jember, 2023)
The history of Islamic thought as a religion has displayed many patterns and patterns of thought in it, including traditional-style thinking which is growing rapidly in Indonesia. Adherents of traditionalism Islam are usually conservative, which tends to move radically as in Turkey and Pakistan, but the reality is that in Indonesia, adherents of this ideology tend to be moderate in their socio-political movements, for example the founders and leaders of the Nahdatul Ulama (NU) organization who accept Pancasila. as the basis of the Indonesian state as a form of their tolerance and moderation. However, along with the development of science and technology, NU leaders and the younger generation are considered by many observers to be no longer traditional as their predecessors. Therefore, in this article, the author will describe the ideology of traditionalism and the transformation of thought within the Nahdatul Ulama (NU) organization group as the largest Islamic mass organization in Indonesia